(untitled) (Islas, 2026)
Introduction: This study analyzes the historical evolution of citizen petitioning in the Republic of Cuba (1902–1959) as a mechanism of citizen participation within the republican model of citizenship. It examines how this practice, although constitutionally recognized, operated in practice as an instrument of oversight, resistance, and political mobilization. The relevance of the topic lies in its potential to make visible the tensions between formal legality and real participation in fragile republican contexts. Methods: A qualitative, historical-comparative approach is adopted, with an exploratory-descriptive design. Primary sources—such as constitutions, manifestos, press materials, and documents from student, labor, and political organizations—are triangulated with secondary sources from recent political historiography. The analysis is conducted through thematic content analysis, articulated with categories drawn from republican political theory, particularly those of Jürgen Habermas and Philip Pettit. Results: Citizen petitioning was legally recognized but politically constrained by clientelism, authoritarianism, and repression. Nevertheless, it was reappropriated by influential social actors, who transformed it into a tool for denunciation, pressure, and revolutionary articulation. Particularly noteworthy is the transformation of petitioning from a reformist instrument into a means of constituent contestation. Conclusions: Citizen petitioning functioned as a link between pseudo-republican institutional structures and opposition or resistance. Although it failed as a formal channel of dialogue, it made it possible to render social demands visible and to foster civic awareness. Its historical analysis shows how limited forms of citizen participation can erode authoritarian regimes and contribute to structural change. This research redefines citizen petitioning as a political category and a tool for democratization, beyond its merely legalistic or formal use.